An efficiently parallelized high-order aeroacoustics solver using a characteristic-based multi-block interface treatment and optimized compact finite differencing - Khanal, Bidur; Saddington, Alistair J.; Knowles, Kevin (MDPI, 2017)
This paper presents the development of a fourth-order finite difference computational aeroacoustics solver. The solver works with a structured multi-block grid domain strategy, and it has been parallelized efficiently by using an interface treatment based on the method of characteristics. More importantly, it extends the characteristic boundary condition developments of previous researchers by introducing a characteristic-based treatment at the multi-block interfaces. In addition, most characteristic methods do not satisfy Pfaff’s condition, which is a requirement for any mathematical relation to be valid. A mathematically-consistent and valid method is used in this work to derive the characteristic interface conditions. Furthermore, a robust and efficient approach for the matching of turbulence quantities at the multi-block interfaces is developed. Finally, the implementation of grid metric relations to minimise grid-induced errors has been adopted. The code was validated against a number of benchmark cases, which demonstrated its accuracy and robustness across a range of problem types